Factores de riesgo psicosocial y su incidencia en la satisfacción laboral del personal del servicio de clínica del hospital Isidro Ayora de Loja, año 2018 - Medina Alvarado, Jenny Gabriela (2019)
The main objective of this research work is to analyze how psychosocial risk factors influence the job satisfaction of the Isidro Ayora de Loja hospital clinic staff, year 2018, and among the specific objectives are to identify the different factors of psychosocial risk that affect the workers of the clinic service of the Isidro Ayora de Loja hospital, and Determine the level of job satisfaction in the staff of the clinic service of the Isidro Ayora de Loja hospital. Try to explain the impact that staff and structure have on behavior within the service, it was carried out through the respective surveys of both psychosocial risk factors and job satisfaction, which were prepared based on a Likert scale, which It measures the perception and expectations of workers. Regarding job satisfaction, the theories of multiple causality Heirinch (1931) and the adjustment theory Person around Harrison (1978) were taken into account, since they are the theories that most focus on psychosocial risk factors, the same as They were of great importance to elaborate the respective survey, also for the study of job satisfaction the theories of Herzberg and Maslow's theory were determined, so they are the ones that give more relevance to the study. Once the survey research technique was applied, it was obtained as results that, in terms of factors, workplace conditions, workload, content and characteristics of the task, work role and career development, social interaction and organizational aspects, performance compensation, all of them are in a range that almost never intervene in their work unlike the labor demands that are almost always present. While with respect to job satisfaction its dimensions of significance are in a satisfied range, except for working conditions, since within it there are small anomalies, although they are not too noticeable, but in a way they are not liked by workers, concluding thus with the determination of an adequate labor satisfaction of the public servants of the clinic service.